THE INFLUENCE OF HALAL LABELS, PRODUCT QUALITY, AND LIFESTYLE ON THE PURCHASE DECISION OF IMPORTED PRODUCTS (IN PACKAGING): PENGARUH LABEL HALAL, KUALITAS PRODUK, DAN GAYA HIDUP ‎TERHADAP KEPUTUSAN PEMBELIAN PRODUK IMPOR (DALAM KEMASAN)‎ - Rispan Rispan; Marliyah Marliyah; Rahmi Syahriza (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the influence of halal labels, product quality, and lifestyle on the purchase decision of packaged imported food products by students of State Islamic Religious Universities (PTKIN) in North Sumatra.The phenomenon of increasing consumption of imported products among Muslim students raises questions about the extent to which religious, rational, and psychological factors play a role in determining purchasing decisions. This study uses a quantitative method with a multiple linear regression approach. Data was obtained through the distribution of questionnaires to 100 PTKIN student respondents in North Sumatra who were selected using the purposive sampling technique. Data analysis is carried out with the help of SPSS software. The results of the study show that three independent variables, namely halal labels, product quality, and lifestyle, have a significant effect on the purchase decision of imported food products in packages. Halal labels are the dominant factor that influences purchase decisions because they provide a guarantee of halal and consumption safety for Muslim students. Product quality has also proven to be an important consideration in assessing the feasibility and quality of the product, while lifestyle reflects the psychological factors that encourage students to choose products according to their trends and self-image. These findings suggest that college students' purchasing decisions are not only driven by religious values, but also by rational considerations and modern lifestyles. The implications of this research encourage business actors to pay attention to halal aspects, maintain product quality, and adjust marketing strategies to the characteristics of young Muslim consumers.